PERANAN FATAHILAH ULAMA ASAL ACEH DALAM PENYEBARAN DAN PENDIDIKAN ISLAM DI JAYAKARTA (THE ROLE OF FATAHILAH ULAMA FROM ACEH IN THE DISSEMINATION AND EDUCATION OF ISLAM IN JAYAKARTA) - Muammar Muammar (AL-ILMU, 2023)
Fatahilah is a figure from Samudera Pasai who played a role in the spread of Islam in Sunda Kelapa which later changed to Jayakarta. Fatahilah son born in Pasai, son of Maulana Qadhi Ibrahim Syarief Bi Inayatilah. When Samudera Pasai was defeated by the Portuguese, Fatahilah carried out the Hajj to Mecca and fostered relations with the Islamic world to liberate Samudera Pasai. After returning from Mecca, Fatahilah returned to Samudera Pasai. Then, because Samudera Pasai was still controlled by the Portuguese, Fatahilah moved to the Kingdom of Demak in Java. Sultan Trenggono Raja Demak married his sister to Fatahilah. Fatahilah carried out reforms in the Islamic education system in the Kingdom of Demak. Shortly after that Fatahilah also gathered strength to fight the Portuguese who wanted to control Sunda Kelapa. In 1527 AD there was a war between Fatahilah against the Portuguese. In this war the Portuguese suffered defeat and were forced to leave Sunda Kelapa. After this war Fatahilah changed the name Sunda Kelapa to Jayakarta. After mastering Jayakarta, Fatahilah actively taught Islamic education to the residents of Jayakarta and developed the port of Jayakarta. Fatahilah was then involved in several conquests in Java. In 1570 AD Fatahilah, after fighting for most of his life for the glory of Islam, returned to Rahmatullah. His struggle and persistence in fighting for Islam must be emulated. Keyword : History of the Spread of Islam and Education